Dependencia serial de largo plazo en el índice bursátil chileno, a través del coeficiente de Hurst y Hurst ajustado - Acuña-Opazo, Christian (2017)
Purpose – This research examined the existence of long-term memory by calculating the coefficient of Hurst and Hurst set, and the analysis of characteristics of chaotic structures in the series of stock market of Chile, specifically through the Selective Price Index Shares. Design/methodology/approach – A brief analysis of the market was developed, according to Box and Jenkins methodology. The validity of the results was performed by means of the test proposed by Brock, Dechert and Scheinkman. Secondly, we proceeded to analyze the dynamics and patterns of the index and its performance, to see if there was evidence of long-term memory. Findings – The results demonstrate the presence of long-term memory in the Chilean stock market, determined by stock index in two scales, daily and quarterly, which also corroborates results obtained by other authors, confirming the use of the methodology Range Re-scalded for the identification and determination of long-term memory in a time series. Originality/value – This study will allow future researchers to perform similar analyzes in other markets, providing a new approach when analyzing the long-term memory and the factors that affect it.